Study between solvatochromism and steady-state and time-resolved fluorescence measurements of the Methylene blue in binary mixtures. (August 2015) - Santin, Luiza R.R.; dos Santos, Sandra C.; Novo, Diogo La Rosa; Bianchini, Daniela; Gerola, Adriana P.; Braga, Gustavo; Caetano, Wilker; Moreira, Leonardo M.; Bastos, Erick Leite; Romani, Ana Paula; de Oliveira, Hueder P.M.
Abstract: In this work, the study on the influence of binary mixtures of solvents (water-acetonitrile, water-ethanol and water-glycerol) upon the spectroscopic properties of methylene blue (MB) was done. In addition, the photophysical characterization of the MB in different concentrations in the solvent mixtures was done. In the mixtures, the increase in the quantity of water has decreased the fluorescence quantum yield together with other photophysical alterations. The studies of time-resolved fluorescence have demonstrated a first-order decay, with lifetimes between 328 and 550 ps. These values increase as the organic solvent proportion is increased. The results have shown a direct relationship between the viscosity and the rotational lifetime, correlating with the interference in the processes of deactivation of the excited state, which are slower in media with higher viscosity. The conformation of the clusters in the binary mixtures was also identified as a key factor to determine the results obtained in this work. Highlights: We study the spectroscopic properties of methylene blue in the binary mixtures. The increase in the quantity of water has decreased the fluorescence quantum yield. Lifetimes show a first-order decay and relationship with the viscosity. Solvatochromism and clusters were identified as a key factor the results. The present results are of fundamental importance in PDT.